Heat-insulating / flame-retardant sheet, and battery pack and battery module package using same
By using heat-insulating/flame-retardant sheets made of materials such as silica inorganic fibers, glass fibers and fiber minerals with hydroxyl groups, the problem of insufficient heat-insulating and flame-retardant performance in the prior art at high temperatures is solved, and the problem of insulating and flame-retardant performance in the prior art is achieved. Effective protection and thermal insulation effect of lithium-ion batteries in the case of thermal runaway.
Patent Information
- Application Number
- CN202380043722.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to provide effective heat insulation and flame retardant properties at high temperatures, especially when lithium-ion batteries are thermally out of control, traditional heat insulation sheets fail in flames above 1000°C and cannot maintain shape, affecting the battery pack. safety.
Made of heat-insulating/flame-retardant sheets composed of silica inorganic fibers with hydroxyl groups, glass fibers, fiber minerals and hydrophilic aerogel particles, made by wet papermaking process to ensure that the sheet remains in shape at high temperatures And provide excellent thermal insulation and flame retardant properties.
The sheet can be maintained in a flame above 1000°C for 10 minutes, effectively slowing down the thermal runaway of lithium-ion batteries, preventing heat spread, and showing excellent thermal insulation performance in conventional use, reducing bulk density, and is suitable for battery packs and modules Thermal insulation and protection of the group.
Smart Images

Figure CN119301803A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat-insulating / flame-retardant sheet positioned between battery cells in a battery pack or battery module used as a power source for an electric motor of a pure electric vehicle or a hybrid electric vehicle, and also relates to a heat-insulating / flame-retardant sheet that can be used for the heat-insulating / flame-retardant outer shell of a battery pack and / or battery module including a plurality of battery cells. The present invention also relates to a battery pack and / or battery module package using the heat-insulating / flame-retardant sheet. Background Art
[0002] A pure electric vehicle or hybrid electric vehicle driven by an electric motor is equipped with a battery pack as a power source, in which battery cells are connected in series or in parallel to form a module. As the battery cell, lithium-ion secondary batteries having high capacity and providing high output are mainly used.
[0003] When the temperature of a battery cell in a battery module rises rapidly due to a short circuit or overcharge, the battery cell may trigger thermal runaway, and the thermal runaway may spread to adjacent battery cells. In addition, in the case of thermal runaway, the battery cell may eject hot lithium electrolyte, causing serious events such as explosion.
[0004] To reduce the risks associated with thermal runaway within the battery module, e.g. Figure 1 As shown, it is proposed to place a heat insulating / flame retardant sheet 10 between battery cells 11 and 11. The sheet 10 can slow down the spread of thermal runaway and can inhibit the fire caused by the fire of the battery cell from spreading. A plurality of battery cells are usually packaged together in a housing 12.
[0005] exist Figure 2 In a typical package of the battery module shown, rectangular battery cells 11' are arranged in parallel, housed in a housing 12', and then sealed with a cover 12'a of the housing 12'. A heat-insulating / flame-retardant sheet 10 is attached to the back of the cover 12'a using an adhesive 10a. The sheet 10 can inhibit the spread of flames and / or hot lithium electrolyte from battery cells under thermal runaway, thereby preventing damage to peripheral devices.
[0006] Mica sheets (sheets containing at least 80% mica) have been used as conventional materials with similar heat and fire resistance properties. However, because the bulk density of mica sheets is high, a lighter sheet that provides nearly the same level of heat insulation and flame retardancy, especially for pure electric vehicles, is needed.
[0007] For a light, heat-insulating and fire-resistant sheet, a woven fabric, non-woven fabric or paper made of inorganic fibers has been proposed. Alumina fiber is an inorganic fiber that is excellent in terms of high heat resistance (melting point is about 2000°C), fire resistance and high insulation, but its price is higher than other inorganic fibers, so it is not suitable for use as a constituent fiber of a sheet. In this case, a heat-insulating sheet made of a combination of inorganic fibers and inorganic particles has been proposed. The sheet can meet the requirements of heat insulation performance and flame retardancy.
[0008] For example, JP2021-531631A (Patent Document 1) proposes a refractory material comprising: two glass fibers having different diameters; a mixture of at least two particulate fillers selected from the group consisting of glass bubbles, kaolin, talc, mica, calcium carbonate, and trihydrate alumina; and an inorganic binder. The refractory material is provided in the form of a sheet made by papermaking technology.
[0009] In addition, WO2019 / 187313 (Patent Document 2) proposes a heat-insulating sheet sandwiched between battery cells stacked in a battery pack, and multiple battery cells are fixed in a stacked state. The heat-insulating sheet is an inorganic fiber sheet, and inorganic particles (inorganic hollow particles or inorganic foam particles) are embedded in the gaps between inorganic fibers. Examples of inorganic fibers include magnesium silicate (sepiolite), rock wool, ceramic fiber, glass fiber, potassium titanate fiber, and calcium silicate. Example 1 discloses a heat-insulating sheet produced as follows: a slurry is prepared, the slurry containing 10% by weight of glass fiber, 10% by weight of nylon fiber, and 80% by weight of magnesium silicate (sepiolite), and the slurry is used for papermaking to obtain a sheet web, which is then dried and hot pressed to produce an inorganic fiber sheet with a thickness of 0.7 mm. The produced inorganic fiber sheet is sandwiched between polyethylene films (50 μm thick) by an adhesive to obtain a heat-insulating sheet. Note that embodiments containing inorganic particles are not disclosed.
[0010] JP2021-034278A (Patent Document 3) proposes a thermal insulation sheet obtained by using a slurry through a papermaking process, wherein the slurry is prepared by dispersing two inorganic particles (the first particle is silica nanoparticles, and the second particle is metal oxide particles such as titanium dioxide and aluminum oxide), linear or needle-shaped inorganic fibers (glass fibers in the embodiment), and optional adhesives (organic adhesives such as polymer flocculants and acrylic emulsions, and inorganic adhesives such as silica sol and alumina sol) in water. Silica nanoparticles can act as thermal insulation materials, and the higher their content, the stronger the thermal insulation performance. Based on this, it is proposed that the entire thermal insulation sheet contains 50 to 80 weight percent of the first inorganic particles, the second inorganic particles, and the inorganic balls in terms of amount.
[0011] In the embodiment, a thermal insulation sheet obtained by a papermaking process using a slurry including 8 wt % of pulp fibers in addition to the above-mentioned constituent components is disclosed.
[0012] JP6997263B and JP7000626B (Patent Documents 4 and 5) propose a heat transfer suppression sheet comprising two inorganic fibers of different diameters and inorganic particles capable of providing a heat insulation effect. The inorganic particles include oxide particles such as alumina and titanium dioxide, and porous particles or hollow particles with high porosity. Regarding these two inorganic fibers, the first fiber has a larger diameter and is linear, while the second fiber has a smaller diameter and is dendritic. These documents describe that the fibers in these combinations can be entangled together to stably hold the inorganic particles even when the amount of inorganic particles is 30 to 90% by weight, and the heat transfer suppression sheet can withstand thermal runaway occurring at high temperatures. However, these documents do not disclose the specific species or types of the first inorganic fiber and the second inorganic fiber. Regarding the manufactured heat transfer suppression sheet, no content is disclosed regarding the heat insulation effect or preventing powder from falling off.
[0013] Aerogel (porous silica particles) is known as a type of porous particle excellent in heat insulation performance.
[0014] JP2015-163815A (Patent Document 6) proposes a heat insulating material (heat insulating sheet) in which 35 to 210 parts by weight of aerogel particles (average particle size of 2 to 140 μm and specific surface area of 400 m2) with high heat insulating effect are mixed per 100 parts by weight of main fibers. 2 The thermal insulation sheet further comprises at least one water-soluble polymer selected from the group consisting of a cationic polymer and an amphoteric polymer, and / or a binder comprising synthetic fibers having a relatively low melting point.
[0015] The main fibers include synthetic fibers such as polyester fibers and aramid fibers, and inorganic fibers such as ceramic fibers, alumina fibers, and glass fibers (
[0018] ). However, the sheets produced in the examples are only sheets using organic fibers such as pulp, polyester fibers, and vinylon binder fibers.
[0016] It is disclosed that since methyl silicate particles are anionic or amphoteric, using a cationic polymer and / or an amphoteric polymer as a binder can promote the flocculation of pulp and porous silica particles and improve the yield.
[0017] In a specific embodiment, main fibers (organic fibers such as pulp, polyester fibers, and vinylon binder fibers), aerogels, and water-soluble polymers are added to water and stirred to prepare papermaking slurry, and a thermal insulation sheet is produced by papermaking technology. The obtained thermal insulation sheet is wrapped around a paper cup or a stainless steel rod, and the temperature of the surface of the thermal insulation sheet is monitored for 60 seconds in both cases of pouring hot water (95°C) into the paper cup and heating the stainless steel rod to 100°C. The measurement results are shown.
[0018] Further, JP2020-200901A (Patent Document 7) proposes a thermal insulation sheet comprising a thermal insulation component having many nanoscale pores, such as aerogel particles, glass beads or ceramic beads, and biosoluble rock wool as a substrate fiber. The document discloses a felt-like or paper-like thermal insulation sheet having a thickness of 1.72 to 6.3 mm, which is formed by a slurry containing fibers, thermal insulation components and a binder by papermaking technology (Table 1 in the embodiment).
[0019] In the present disclosure, starch, polyvinyl alcohol, acrylic starch and acrylic polyvinyl alcohol are listed as the binder (
[0025] ), and 50 to 300 parts of the binder should be mixed with 100 parts by weight of the base fiber (rock wool) (
[0026] ). In the example of Patent Document 7, an aerogel dispersion is added to a biosoluble rock wool dispersion as a fiber dispersion to prepare a papermaking slurry. The aerogel dispersion is prepared by mixing the aerogel with an aqueous solution containing the binder.
[0020] This papermaking slurry was applied to a laminate of filter paper and a web, and the web and filter paper in a stacked state were heated and pressurized to produce a thermal insulation sheet. In the examples, the thermal conductivity (hot wire method) of the produced thermal insulation sheet was measured and the results are shown.
[0021] Prior art
[0022] Patent Literature
[0023] Patent Document 1: JP2021-531631A
[0024] Patent Document 2: WO2019 / 187313
[0025] Patent Document 3: JP2021-034278A
[0026] Patent Document 4: JP6997263B
[0027] Patent document 5: JP7000626B
[0028] Patent Document 6: JP2015-163815A
[0029] Patent Document 7: JP2020-200901A Summary of the invention
[0030] Technical problem to be solved by the invention
[0031] As a typical inorganic fiber, conventional glass fibers such as E glass fibers are inexpensive but can be used at temperatures as high as 700°C or less. When thermal runaway occurs at a temperature higher than 700°C, the glass fibers melt, so that a sheet made of the glass fibers cannot maintain its original shape. Patent Document 1 discloses in an example that in the presence of clay, mica, and glass bubbles, by reducing the content of the glass fibers to a range of 7 to 25% by weight, the sheet has durability during a gas torch flame test.
[0032] Evaluation tests including a gas torch flame test were conducted on a multilayer sheet. The multilayer sheet is made by laminating inorganic paper with sodium silicate as an inorganic binder, followed by pressurization and drying. The flame test results showed that thin multilayer sheets produce holes when burned.
[0033] In Patent Document 2, although the content of glass fiber is set to 10% by weight or less, there is no example of a sheet containing particles. Document 2 proposes that if the sheet contains inorganic particles such as aerogel, the sheet should be sandwiched with a plastic film. The heat insulating sheet inserted between the batteries is retained by the batteries. Therefore, even if the plastic film burns out during thermal runaway, the heat insulating sheet can still remain between the batteries and can suppress heat transfer. However, in the case of Figure 2 When the heat-insulating sheet containing inorganic particles is attached to the top of the housing for use, even if the sheet is wrapped with a plastic film, the particles will fall off once the film is burned.
[0034] Any sheet proposed in Patent Documents 3 to 5 contains 30% by weight or more, or even 50% by weight or more, of inorganic particles in terms of content. In Patent Document 3, for a paper having a thickness of 1 mm containing 10% by weight of glass fibers and 8% by weight of pulp fibers, a thermal conductivity of up to 850°C was measured by changing the content ratio of silica nanoparticles and titanium dioxide particles, but no flame test was conducted. If the paper is fixed to the top of a housing for insulation, it is unclear whether the paper can maintain its original shape when exposed to a flame close to 1000°C. Further, Patent Documents 4 and 5 do not provide specific examples to show the insulation effect of the particles still remaining in the sheet.
[0035] Patent Document 6 discloses the test results of the heat insulation effect of aerogel, but the test was conducted only using a heat source with a temperature of about 100°C. For a sheet material used to protect lithium-ion battery cells from thermal runaway, since the temperature of the battery cells that undergo thermal runaway rises to 500°C or more, it is necessary to have flame retardant and heat insulation properties that can withstand high temperatures of 500°C or more. However, Document 6 does not clarify whether the proposed sheet material can meet these requirements.
[0036] Patent Document 7 proposes using the sheet as a material for heat-insulating containers for medicines or foods (
[0002] ) and using the sheet for heat insulation of electronic components (
[0003] ), but does not disclose using the sheet as a protective sheet for preventing thermal runaway of lithium-ion batteries. Although the results of thermal conductivity measurements are given, the flame retardancy and heat insulation properties of the sheet at 600°C or above are not disclosed. It is unclear whether the sheet meets the requirements for flame-retardant and heat-insulating protective sheets at such high temperatures.
[0037] The biosoluble rock wool used as the base fiber of the sheet is an inorganic fiber and is non-flammable (fire-resistant). In addition, the biosoluble rock wool can withstand heating up to about 700°C. On the other hand, rock wool contains non-fibrous particles (called crushed particles), which are parts that are not fiberized in the manufacturing process. Rock wool is made by melting raw materials such as slag and rock in an electric furnace at 1500-1600°C, and using centrifugal force to blow the molten material to solidify it in the air. In this method, non-fibrous particles may be reduced in the papermaking process, but it is difficult to completely remove them. Therefore, the thermal insulation sheet containing biosoluble rock wool contains a certain proportion of crushed particles. Such crushed particles may affect the thermal insulation performance and flame retardant properties. In addition, non-fibrous particles may damage the outer wall of the battery cell in contact with the sheet.
[0038] Under the above circumstances, the object of the present invention is to provide a thin and light heat-insulating / flame-retardant sheet having a thickness of more than 0.5 mm, 1 mm or more and 3 mm or less, preferably 2 mm or less. The sheet can maintain its original shape for at least 10 minutes even when exposed to a flame at a temperature close to 1000°C, and can have both flame-retardant and heat-insulating properties.
[0039] Solutions for solving the above technical problems
[0040] The present inventors have investigated fibers and sheets to produce a thin, lightweight sheet that provides thermal insulation and flame retardancy both under conventional conditions and when exposed to flames (above 1000°C). Conventional use refers to controlling the temperature increase to prevent conditions that trigger thermal runaway.
[0041] Lithium-ion batteries used as power sources for EV cars are made of stacked battery cells. In order to ensure heat resistance, the heat-insulating / flame-retardant sheets placed between the battery cells should be made of inorganic materials as the main component and should be thin and light. It is known that the wet papermaking method is a method for producing a thin sheet with a thickness of more than 0.5 mm, 1 mm or more and less than 3 mm, preferably less than 2 mm, using inorganic materials.
[0042] Aerogel particles, which are well known as a high thermal insulator, exhibit excellent thermal insulation due to nano-scale air pockets. Aerogel has a low density and a hydrophobic surface. This makes it difficult for aerogel particles to become entangled with fibers in a wet papermaking process when water is used as a dispersion medium. Aerogel particles should be uniformly dispersed in a slurry or fiber-containing suspension for papermaking and mixed with fibers in order for the aerogel to exert its thermal insulation effect.
[0043] In addition, it is known that the thermal insulation effect of aerogel particles decreases in the high temperature range above 500° C. where the proportion of radiant heat increases. Therefore, for thermal insulation at high temperatures where thermal runaway occurs, another thermal insulation mechanism is required in addition to silica aerogel particles.
[0044] On the other hand, although clay minerals can also function as an excellent flame retardant, clay has a high thermal conductivity. This means that the higher the content of clay contained in the sheet, the lower the thermal insulation performance of the sheet. Furthermore, in the wet papermaking method, clay clogs the mesh during filtration and dehydration, which actually makes it difficult to produce a sheet with a thickness of more than 1 mm. In this regard, the sheet should be obtained by laminating a plurality of sheets of paper, as in the inorganic paper produced in Patent Document 1.
[0045] The inventors have found that silica inorganic fibers having hydroxyl groups at the ends can absorb thermal energy through a dehydration condensation reaction. This helps to mitigate the temperature surge at the early stage of thermal runaway that occurs when exposed to high temperatures.
[0046] For silica inorganic fibers having hydroxyl groups at the ends, this reaction occurs at about 300-600°C, producing water and consuming heat energy to evaporate the water. The dehydration condensation reaction is an endothermic reaction, so the temperature rise is suppressed, thereby delaying the initial temperature rise of the silica inorganic fibers.
[0047] The inventors believe that when silica inorganic fibers are included as substrate fibers in a heat insulating / flame retardant sheet, the silica fibers enhance thermal insulation. Silica fibers can assist in thermal insulation at high temperatures under normal conditions, even when the thermal insulation effect of aerogel particles is reduced. In addition, silica inorganic fibers can act as flame retardants to prevent temperature surges that trigger thermal runaway. These phenomena may reduce the risk of thermal runaway spreading or diffusing in lithium-ion batteries. Thus, the present invention is completed.
[0048] The present invention provides a heat-insulating / flame-retardant sheet, comprising: 25 to 70 weight percent of silica inorganic fibers having hydroxyl groups; 2 to 25 weight percent of glass fibers; 5 to 40 weight percent of fiber minerals; 3 to 20 weight percent of adhesives; and 0 to 45 weight percent of heat-insulating inorganic particles, wherein the thickness of the heat-insulating / flame-retardant sheet is less than 3 mm, wherein the heat-insulating inorganic particles comprise hydrophilized aerogel particles, which are obtained by treating the surface of hydrophobic aerogel particles having a porosity of more than 80% and an average particle size of 5 to 200 μm.
[0049] Preferably, the weight ratio of the inorganic silica fibers to the glass fibers, ie, inorganic silica fibers / glass fibers, is 30 / 1 to 1.5 / 1.
[0050] Preferably, the contact angle between the surface of the hydrophobic aerogel particles and water droplets is preferably greater than 100 degrees.
[0051] The hydrophilized aerogel particles are obtained by contacting the surfaces of aerogel particles with an organic solvent, a surfactant or a hydrophilic polymer.
[0052] According to one aspect of the present invention, the hydrophilized aerogel particles are obtained by coating at least a portion of the hydrophobic aerogel particles with a hydrophilic polymer. A preferred hydrophilic polymer is a polymer having a hydroxyl group.
[0053] Preferably, the weight of the hydrophilic polymer in the hydrophilized aerogel particles relative to the hydrophobic aerogel particles is 1 / 2 to 1 / 100 in terms of hydrophilic polymer / hydrophobic aerogel particles (weight ratio).
[0054] Preferably, the fiber mineral is at least one selected from the group consisting of sepiolite, palygorskite, potassium titanate whisker and wollastonite.
[0055] Preferably, the adhesive comprises thermoplastic resin fibers and may further comprise an organic flocculant.
[0056] Further, the binder may include an inorganic binder, examples of which include colloidal silica and / or an inorganic metal salt.
[0057] The bulk density of the heat insulation / flame retardant sheet disclosed herein is 100-400 kg / m 3 .
[0058] Another aspect of the present invention provides a method for manufacturing a heat-insulating / flame-retardant sheet containing heat-insulating inorganic particles. The manufacturing method comprises the following steps: preparing a slurry containing a hydrophilized aerogel, wherein the slurry contains silica aerogel particles having a hydrophobic surface, a porosity of 80% or more, and an average particle size of 5 to 200 μm, and dispersing the silica aerogel particles in an aqueous solution containing a hydrophilizing agent;
[0059] adding and mixing the slurry containing the hydrophilized aerogel into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder to prepare a suspension containing 25 to 70 weight % of silica inorganic fibers, 2 to 25 weight % of glass fibers, 5 to 40 weight % of fiber minerals, 3 to 20 weight % of a binder, and more than 0 to 45 weight % of the hydrophilized aerogel; and
[0060] The suspension is used to carry out a papermaking process to obtain a sheet having a thickness of less than 3 mm.
[0061] According to one embodiment, the manufacturing method comprises the following steps: preparing a slurry containing a hydrophilized aerogel, which can be obtained by dispersing silica aerogel particles having a hydrophobic surface, a porosity of 80% or more, and an average particle size of 5 to 200 μm in an aqueous solution of a water-soluble polymer;
[0062] adding and mixing the slurry containing the hydrophilized aerogel into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder containing thermoplastic resin fibers; and
[0063] The resulting mixed liquid is used to perform a papermaking process, followed by heating and pressurization to obtain a sheet having a thickness of less than 3 mm.
[0064] If the slurry containing the hydrophilized aerogel contains a surfactant or an organic solvent, the content of the surfactant is preferably 10 wt % or less, and the content of the organic solvent is preferably 10 wt % or less.
[0065] The present invention includes a battery pack and a battery module each comprising the disclosed heat-insulating / flame-retardant sheet.
[0066] In one embodiment of the battery pack or battery module, the battery pack or battery module includes battery cells connected in series or in parallel housed in a housing, and a heat insulating / flame retardant sheet placed between the battery cells.
[0067] In another embodiment of the battery pack or battery module, the battery pack or battery module includes battery cells connected in series or in parallel, wherein the battery cells are accommodated in a housing, and a heat insulating / flame retardant sheet is attached to the inner wall of the housing in contact with the battery cells.
[0068] Effects of the Invention
[0069] The heat-insulating / flame-retardant sheet of the present invention is light in weight and can exhibit excellent heat-insulating properties in conventional use. In addition, the heat-insulating / flame-retardant sheet can withstand the temperature surge caused by thermal runaway and can be exposed to a flame close to 1000°C for 10 minutes. Therefore, the thermal runaway of lithium-ion batteries can be mitigated. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 A schematic diagram showing the structure of a battery pack with heat insulating / flame retardant sheets interposed between battery cells.
[0071] Figure 2 A schematic diagram showing a structural example of a battery module in which a heat insulating / flame retardant sheet is applied to the cover of the casing.
[0072] Figure 3 A schematic diagram showing the structure of another embodiment of a lithium-ion battery module.
[0073] Figure 4 Shown in Figure 3 A schematic diagram of the structure of an exemplary thermal insulation / flame retardant sheet used in a lithium-ion battery module is shown.
[0074] Figure 5 It is a figure for demonstrating the flame exposure test performed in an Example.
[0075] Figure 6 It is a figure for demonstrating the method of measuring thermal conductivity in Example.
[0076] Figure 7 is an electron microscopic image (magnification 1000 times) of a cross section in the thickness direction of the heat insulating / flame retardant sheet No. 21 produced in Example.
[0077] Figure 8 is an electron microscopic image (magnification 1000 times) of a cross section in the thickness direction of the heat insulating / flame retardant sheet No. 23 produced in Example.
[0078] Fig. 9 This is an electron microscopic image (magnification 1000 times) of the heated surface of the heat insulating / flame retardant sheet No. 21 after the flame exposure test.
[0079] Fig.10This is an electron microscopic image (magnified 1000 times) of the heated surface of the heat insulating / flame retardant sheet No. 23 after the flame exposure test.
[0080] Fig.11 It is a figure for demonstrating the thermal insulation test I performed in an Example.
[0081] Fig.12 This is a photograph of the heated surface of the heat insulating / flame retardant sheet No. 23 produced in Example after being subjected to the heat insulating test I.
[0082] Fig.13 This is a photograph of the heated surface of the heat insulating / flame retardant sheet No. 27 produced in Example after being subjected to the heat insulating test I.
[0083] Fig.14 This is a microscopic image (magnified 100 times) of the heated surface of the heat insulating / flame retardant sheet No. 23 after the heat insulating test I.
[0084] Fig.15 This is a microscopic image (magnified 100 times) of the heated surface of the heat insulating / flame retardant sheet No. 27 after the heat insulating test I.
[0085] Fig.16 This is a microscopic image (magnified 100 times) of the back side of the thermal insulation / flame retardant sheet No. 23 after thermal insulation test I. In the thermal insulation test, the back side was not exposed to the flame.
[0086] Fig.17 This is a microscopic image (magnified 100 times) of the back side of the thermal insulation / flame retardant sheet No. 27 after thermal insulation test I. In the thermal insulation test, the back side was not exposed to the flame.
[0087] Fig.18 It is a figure for demonstrating the thermal insulation test II performed in an Example.
[0088] Fig.19 is a graph showing temperature changes as measurement results of the thermal insulation test II. DETAILED DESCRIPTION
[0089] The heat-insulating / flame-retardant sheet of the present invention is a paper-like sheet of inorganic fibers, comprising silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, a binder, and optionally a certain amount of heat-insulating inorganic particles.
[0090] In particular, the paper-like sheet is a sheet having a thickness of less than 3 mm, preferably less than 2 mm, and can be obtained by a papermaking process using a suspension containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, a binder, and, as required, thermal insulation inorganic particles in a desired proportion.
[0091] <Composition of papermaking suspension>
[0092] First, the papermaking suspension for forming the heat-insulating / flame-retardant sheet of the present invention will be described.
[0093] The suspension contains silica inorganic fibers with hydroxyl groups, glass fibers, fiber minerals, a binder, and optionally a certain amount of thermal insulation inorganic particles in water or an aqueous medium containing an organic solvent or a surfactant. Each component will be described in detail below.
[0094] (1) Silica Inorganic Fiber
[0095] The silica inorganic fiber used in the present disclosure is an amorphous fiber containing SiO2 as a fiber component and having a hydroxyl group at the end.
[0096] The hydroxyl groups contained in the silica inorganic fiber undergo a condensation reaction at about 300°C to 600°C as shown in the following formula (1) to form a siloxane bond (Si-O-Si bond) and generate H2O. The water generated by the condensation reaction evaporates in a high temperature atmosphere. During evaporation, the silica inorganic fiber sheet consumes a certain amount of heat energy for the evaporation of water, thereby delaying the temperature rise of the sheet.
[0097] [Formula 1]
[0098] Si(OSD3OH+HO-Si→Si(OSD4+H2O(1)
[0099] Exemplary silica inorganic fibers having hydroxyl groups are silica amorphous fibers made from silicic acid modified with alumina and typically containing 90-97 wt % silica, about 3-9 wt % alumina, less than 0.5 wt % sodium oxide, and less than 0.5 wt % other components (ZrO2, TiO2, Li2O, K2O, CaO, MgO, SrO, BaO, Y2O3, La2O3, Fe2O3, and mixtures thereof). Si(OH) is present in SiO - Such silica inorganic fibers have a melting point of 1500°C to 1550°C and a heat resistance of 1000°C or more.
[0100] Furthermore, such silica amorphous fibers contain substantially no non-fiber particles (crushed particles). Since crushed particles may deteriorate various characteristics of the fiber and cause changes in performance, fibers without crushed particles are excellent.
[0101] The composition of the inorganic silica fibers used in the present disclosure is not particularly limited as long as the inorganic silica fibers can undergo the dehydration condensation reaction as described above. As the inorganic silica fibers, unsintered BELCOTEX (registered trademark) from BELCHEM GmbH is commercially available.
[0102] Unsintered BELCOTEX (registered trademark) has hydroxyl groups, which are substituted by protons for metal ions or metal oxide ions (e.g., Al2O3) contained in the starting glass material during the process of manufacturing long fibers or short fibers from the starting glass material. 3+ 、TiO 2+ or Ti 4+ 、ZrO 2+ or Zr 4+ ) is generated.
[0103] The silica inorganic fibers used in the present disclosure are short fibers having a diameter of 6 to 13 μm, preferably 7 to 10 μm, and a length of 3 to 30 mm. Alternatively, short fibers having a diameter of about 6 to 13 μm, preferably about 7 to 10 μm, and a length of generally 1 to 50 mm, preferably 3 to 30 mm, and more preferably 3 to 20 mm may be used.
[0104] The papermaking suspension contains silica inorganic fibers at a solid content of 25 wt % or more, 30 wt % or more, 40 wt % or more and 70 wt % or less, 65 wt % or less, or 50 wt % or less. The content of silica inorganic fibers can be appropriately selected within a certain range depending on the content of the thermal insulation inorganic particles and the fiber mineral.
[0105] The content of silica inorganic fibers in the thermal insulation / fire retardant sheet is similar to the solid content of the papermaking suspension.
[0106] If the content of inorganic silica fibers contained in the sheet is too low, the heat energy consumed will be reduced. This may not be able to sufficiently slow down the temperature rise at the beginning of thermal runaway. On the other hand, if the content of inorganic silica fibers contained in the sheet is too high, the content of other components will be relatively reduced. In this way, even if the use of glass fibers can solve the problem of heat shrinkage as described later, the strength such as tensile strength will be reduced, which will lead to impaired handling performance.
[0107] (2) Glass fiber
[0108] The glass fibers contained in the sheet can enhance the tensile strength of the sheet. This means that shrinkage at high temperatures caused by the silica inorganic fibers can be suppressed. In other words, because the glass fibers melt and shrink at high temperatures, especially when exposed to flames, their fiber shape cannot be maintained. In addition, the glass fibers do not exhibit thermal insulation properties. However, in the case of reducing the content of glass fibers in the sheet, the glass fiber melt only invades the gaps between the silica inorganic fibers and spreads in a thin film. This means that at a temperature at which the glass fibers begin to melt and the silica fibers undergo dehydration condensation and shrinkage, the molten glass is trapped between the silica fibers, thereby preventing the molten glass from sagging. The molten glass trapped between the silica inorganic fibers can also offset the shrinkage of the silica fibers. Therefore, even when the thermal insulation / flame retardant sheet such as Figure 2 The molten glass fibers also do not sag when attached to a cover as in the exemplary application shown.
[0109] Regarding the size of the glass fiber, the diameter is about 1 to 10 μm, preferably 3 to 9 μm, and more preferably 4 to 6 μm. The glass fiber should have a sufficient length and durability to be entangled with the silica inorganic fiber and the organic fiber described later. Because the glass fiber melts at a temperature as high as the temperature when exposed to a flame, the molten glass fiber becomes a large glass drop, and the glass drop droops due to its own weight. Therefore, the glass fiber used is preferably a short fiber with a fiber length of 1 to 15 mm, preferably 2 to 10 mm.
[0110] The type of glass fiber used in the present disclosure is not particularly limited. Based on the role of glass fiber in the sheet, glass fiber does not need high heat resistance, so from the viewpoint of availability and cost, it is preferred to use E glass fiber.
[0111] From the perspective of the role of glass fiber, the content of glass fiber in the suspension used for papermaking is more than 2 weight %, more than 5 weight %, and less than 25 weight %, less than 20 weight %, less than 15 weight %, less than 10 weight %, and less than 7 weight %.
[0112] The glass fiber content in the thermal insulation / fire retardant sheet is approximately the same as the solid content in the papermaking suspension.
[0113] In view of the above-mentioned effects of glass fiber, according to the range of the content of silica inorganic fiber, the content of glass fiber in the heat insulation / flame retardant sheet is preferably selected from the above range. Further, the weight ratio of silica inorganic fiber to glass fiber is 30:1 to 1.5:1, preferably 20:1 to 2:1, and more preferably about 10:1 to 3:1.
[0114] If the glass fiber content is too high, the glass fibers tend to have difficulty maintaining their original sheet shape in the high temperature range where the glass melts (over 700°C) or when exposed to flame.
[0115] (3) Fiber Minerals
[0116] The fibrous mineral used in the present invention is a mineral composed of particles in the form of fibers, dendrites, needles, columns or rods. The shape of the particles can be identified by microscopic observation. Therefore, fibrous minerals are sometimes also called clay minerals or mineral fibers.
[0117] The aspect ratio of the fibrous mineral, ie, length / width, is 10 or more, preferably 15 or more, and 200 or less, preferably 150 or less, wherein the length and width correspond to the length and diameter of the fiber, respectively.
[0118] The insulating inorganic particles described later have poor insulating properties at high temperatures (e.g., above 500°C) where thermal runaway occurs, and also do not have flame retardant properties. Clay minerals, on the other hand, have excellent heat resistance and fire resistance. However, clay increases the viscosity of the suspension, which may cause clogging in the papermaking process (particularly the filtration and dewatering process using a mesh). In this regard, fibrous minerals have an advantage because they are not easily clogged.
[0119] From this viewpoint, the average primary particle size of the fiber mineral is 5 μm or more, 10 μm or more, or 20 μm or more, and 200 μm or less, 100 μm or less, 80 μm or less, or 70 μm or less.
[0120] For curved or curled fiber minerals, the diameter of the circle can be used as the average particle size by assuming that the end length of the two-dimensional projection of the curved or curled fiber is a circle. The desired fiber mineral can be obtained by classifying according to the maximum particle size using a sieve.
[0121] As the fibrous mineral, at least one selected from the group consisting of sepiolite, palygorskite, potassium titanate whiskers, and wollastonite is preferred.
[0122] Both sepiolite and palygorskite are layered silicates classified as clay minerals having a fiber morphology. The width corresponding to the fiber diameter is less than 0.1 μm, and the length measurable by microscopic observation (fiber length) is about 150 μm at most.
[0123] Sepiolite is a hydrous magnesium silicate with a banded structure in a ratio of 2:1. Sepiolite is divided into α-type and β-type according to the different origins, and either type can be used. α-type sepiolite has a longer length and higher crystallinity due to the hydrothermal action under high temperature and high pressure conditions. β-type sepiolite is a block or clay-like short fiber, and has a relatively low crystallinity because its origin is shallow sea or lake bottom sediment. In addition, α-type sepiolite can usually be confirmed as a fiber under an electron microscope image (magnification 1000 times), but β-type sepiolite is granular under an electron microscope image (magnification 1000 times), and it is usually difficult to identify as a fiber form.
[0124] The layered structure of sepiolite has a chain structure. Moreover, sepiolite is porous and has a large specific surface area, so it has excellent adsorption properties. Sepiolite with such properties can show thixotropic properties and can be crushed into a fiber form in a slurry with water as a dispersion medium. In addition, sepiolite has plasticity and flexibility and can invade the gaps between fibers, so sepiolite can be used as a binder between fibers after drying and compaction.
[0125] Wollastonite is a metasilicate, a needle-shaped crystal mineral with a length of about 50 μm and a width (fiber diameter) of less than 1 μm.
[0126] Potassium titanate is a needle-shaped single crystal (whisker). The typical fiber diameter of the whisker is 0.1-0.5 μm and the length is 10-50 μm. The length of the whisker that can be used is usually 15-30 μm.
[0127] Such fibrous mineral particles can be entangled with silica inorganic fibers and glass fibers in the papermaking suspension. Therefore, even in the sheet produced by the papermaking method, the fibrous mineral is stably maintained and is not easy to fall off. In addition, the fibrous mineral also helps to strengthen the sheet. In addition, the fibrous mineral particles or the particles entangled with each other are not easy to cause blockage during the filtering and dehydration process. Therefore, the fibrous mineral particles are excellent in operability in the papermaking process.
[0128] On the other hand, other mineral particles, including plate-like clay minerals such as mica and talc, are rarely interwoven with fibers in a slurry state, so these mineral particles may slightly enhance the strength of the sheet, and the firmness and handling properties of the resulting sheet are often insufficient.
[0129] In addition, the fiber mineral can enhance the tensile strength of the sheet under high temperature conditions due to its high heat resistance. This is beneficial because the glass fiber contained in the sheet may not enhance the tensile strength of the sheet under high temperature conditions.
[0130] On the other hand, the thermal insulation effect of these minerals is often not as good as the thermal insulation inorganic particles or inorganic fibers described later. The increase in the content of fibrous minerals leads to a relative decrease in the content of other components that can provide thermal insulation performance. Therefore, too large a content of fibrous minerals may reduce the thermal insulation performance of the thermal insulation / flame retardant sheet.
[0131] For these reasons, the content of the fiber mineral in the thermal insulation / flame retardant sheet in the papermaking suspension is appropriately selected within the range of 5 weight %, 8 weight %, 10 weight %, 15 weight % or more, and 40 weight %, 35 weight %, 30 weight %, or 20 weight % or less, depending on the content of other components.
[0132] (4) Adhesive
[0133] As the binder, an organic binder and / or an inorganic binder may be used. The binder mentioned in the present disclosure includes compounds capable of binding fibers to each other and binding fibers to inorganic particles, and also includes common flocculants used in papermaking or molding involving removal of water.
[0134] A flocculant is a substance that acts like a cross-linking agent to promote the flocculation of fibers and particles contained in a papermaking suspension. Flocculants increase the yield in the papermaking process.
[0135] (4-1) Organic binder
[0136] The organic binder can be used in various forms such as powder, granules, colloidal solution, high viscosity fluid, fiber, etc.
[0137] Examples of fiber binders include thermoplastic resin fibers. In the papermaking process, thermoplastic resin fibers can act as a binder by interweaving with highly elastic glass fibers and / or silica inorganic fibers, or even with thermal insulation inorganic particles.
[0138] In addition, the thermoplastic resin fiber can be softened and melted by heating during the drying process after papermaking, and the fibers can be bonded. Bonding the fibers by heating and pressurizing during the drying process can prevent the rebound of glass fibers or silica inorganic fibers, thereby ensuring that a sheet with a desired thickness is obtained.
[0139] Thermoplastic resin fibers include pulp fibers, polyester fibers (softening temperature: about 240°C, melting temperature: about 255-260°C), polypropylene fibers (softening temperature: about 140-160°C, melting temperature: about 165-173°C), polyethylene fibers (softening temperature: about 100-115°C, melting temperature: about 125-135°C), acrylic fibers (softening temperature: about 190-240°C), polyvinyl chloride fibers (softening temperature: about 60-100°C, melting temperature: about 200-210°C), vinylidene fibers (softening temperature: 145-165°C, melting temperature: about 165-185°C), nylon fibers (softening temperature: about 180°C, melting temperature: about 215-220°C), vinylon fibers (softening point: 220-230°C) and polyvinyl alcohol fibers. It is also possible to use thermoplastic resin fibers having a core-sheath structure in which a core fiber is covered with a resin having a relatively low softening temperature.
[0140] As the organic binder, short fibers of thermoplastic resin fibers having a fiber diameter of 3 μm to 50 μm, preferably 5 μm to 30 μm, and a fiber length of 1 to 20 mm, preferably 3 to 10 mm are preferably used. Since the thermoplastic resin fibers need to be evenly entangled with the inorganic fibers constituting the main body of the heat insulating / flame retardant sheet, the preferred thermoplastic resin fibers have a length similar to that of inorganic fibers such as glass fibers and silica inorganic fibers.
[0141] As adhesives, in addition to this fiber organic adhesive, powders or fluids of organic polymers can also be used, for example, latexes such as acrylic latex and (meth)acrylic latex, powdered thickening substances such as polyvinyl alcohol powder and starch, copolymers of styrene and butadiene, vinyl pyridine, acrylonitrile, and copolymers of acrylonitrile and styrene.
[0142] These organic binders give the wet-laid sheet the strength it needs in the papermaking process. After papermaking and after the dispersion medium is removed, the wet-laid sheet solidifies, but can be softened again by heating, which facilitates the required processing such as slitting or folding.
[0143] The organic binder softens and deforms during normal use and during the temperature rise process until the glass fiber melts, thereby being embedded in the gaps between the inorganic particles held by the inorganic fibers. This allows the inorganic particles to be maintained in a stable state.
[0144] Furthermore, polymer flocculants such as polyacrylamide, acrylamide-sodium acrylate copolymer, sodium polyacrylate, etc. contained in the organic binder may also be included. In the wet papermaking method, particles smaller than the mesh will pass through the mesh, and these particles cannot be filtered out when the mesh is used for dehydration. In order to solve this problem, a polymer flocculant is added to the fiber-containing liquid (papermaking suspension) to form a sufficiently large flocculent that is separated from the filtrate, thereby obtaining the flocculent to be formed. In view of the effect of the polymer flocculant, it is preferred to add the agent used as the organic binder to the fiber-containing liquid in which the fibers and particles are uniformly mixed or to the mixture of the fiber-containing liquid and the slurry containing the thermal insulation particles.
[0145] The organic binder can be used alone or in combination of two or more. When two or more are used in combination, it can be a combination of organic binders of different forms (e.g., a combination of organic fiber and latex) or a combination of binders of different functions (e.g., a combination of organic fiber and polymer flocculant).
[0146] A necessary and sufficient amount of organic binder may be included so that the sheet obtained by the papermaking technology can have flexibility to adapt to post-treatment or heat treatment, or can inhibit the expansion and contraction of the sheet due to conventional temperature changes. If the content of organic fibers is too high, the heat resistance of the sheet may be reduced. Further, at high temperatures exceeding conventional temperatures, such as exceeding about 200°C, the organic components may increase the temperature of the sheet due to their own oxidative exothermic reactions, or may decompose and produce gases. These may cause the risk of smoke, fire or explosion. For these reasons, the solid content in the papermaking suspension is 1% by weight or more, 3% by weight or more, 5% by weight or more, and is less than 10% by weight or less than 8% by weight.
[0147] (4-2) Inorganic binder
[0148] As the inorganic binder, colloidal oxides such as colloidal silica, alumina sol, and titania sol; water glass or calcium silicate; and aluminum sulfate classified as a fixing agent or an inorganic flocculant can be used.
[0149] The colloidal silica particles can enter the gaps between the fibers and solidify in the gaps through drying, thereby playing the role of a binder between the glass fibers and the silica inorganic fibers.
[0150] Aluminum sulfate can improve drainage and fiber yield in the wet papermaking process, so aluminum sulfate is usually added as a fixative or retention aid in the papermaking process.
[0151] The inorganic binder may be used alone or in combination of two or more. The content of the inorganic binder in the suspension for papermaking is about 1 wt % or more, 3 wt % or more, and 10 wt % or less, 7 wt % or less, and 5 wt % or less.
[0152] Either an organic binder or an inorganic binder may be used, or both may be used in combination. When both are used in combination, the content of the binder in the papermaking suspension is 3 to 20% by weight, preferably 5 to 15% by weight.
[0153] (5) Insulating inorganic particles
[0154] Examples of thermally insulating inorganic particles used in the present disclosure include: porous or hollow inorganic particles, such as silica aerogels, glass bubbles and glass spheres, etc.; nanoparticles that form agglomerates that can act like porous particles; ceramic particles that scatter radiant heat, such as titanium oxide, aluminum oxide and silica that does not have a binder function (e.g., crystalline silica powder, amorphous silica and fumed silica), etc.
[0155] Among them, hollow or porous silica particles and nanoparticles are preferred because they can exert a heat insulating effect due to the presence of air and contribute to weight reduction. Porous silica particles such as silica aerogel are more preferred.
[0156] The silica particles used as thermal insulation inorganic particles are aggregates or agglomerates of nano-sized particles (about 5 to 50 nm) and form a network structure having a porosity of 50% by volume or more with nano-sized pores. Such silica particles are manufactured by a sol-gel method, a dry method (fumed silica), a wet method (precipitated silica), etc. The size and state of the aggregates or agglomerates vary depending on the manufacturing method and manufacturing conditions.
[0157] Wet-process silica (precipitated silica) is usually synthesized using sodium silicate synthesized from silica sand, soda ash, and mineral acids in water. Wet-process silica is obtained as agglomerates (i.e., as clusters of secondary particles) with an amorphous macroporous structure and can act like porous particles.
[0158] The silica particles produced by the sol-gel method are aggregates having a network structure formed by aggregating nano-sized particles (about 5 to 50 nm) and connecting these particles together through silanol bonds. The silica particles are equivalent to porous particles as primary particles, have nano-sized pores, and a porosity of 70% by volume or more, preferably 80% by volume or more, and more preferably 90% by volume or more.
[0159] The preferred silica particles are hydrophobic aerogels with nanometer-sized pores, which provide long and tortuous gas paths. Such aerogels can exhibit thermal and electrical insulation based on the gas paths.
[0160] Hereinafter, as representatives of the heat-insulating inorganic particles, hydrophilized aerogel particles and nanoparticle aggregates having a hydrophilic surface will be described.
[0161] (5-1) Hydrophilized aerogel particles
[0162] Porous silica aerogel is produced by a sol-gel method. Specifically, a sol containing at least one tetrafunctional silane compound in addition to a difunctional silane and a trifunctional silane is subjected to a crosslinking reaction to form a gel. The obtained wet gel is dried to obtain a porous silica aerogel. During the drying process, water and / or organic solvents on the surface and inside of the wet gel are removed, or replaced with organic solvents (solvent exchange). If necessary, the wet gel is shaped before drying. Regarding the drying technique, supercritical drying or normal pressure drying can be appropriately selected according to the type of organic solvent.
[0163] Therefore, the pore size of the produced xerogel or aerogel is about 1 to 20 nm, which is smaller than the mean free path of gas molecules.
[0164] Silica aerogel produced by the sol-gel method has silanol groups on the surface. The silanol groups are terminated with hydrophobic groups using a silanizing agent or the like to produce aerogel particles having a hydrophobic surface. Individual silica particles contained in the aggregate have a hydrophobic surface and are hydrophobic in their individual pores. Even in a slurry in which the dispersion medium is water, the hydrophobic aerogel can prevent water from entering the pores. As a result, the pores are still filled with air, thereby reducing the thermal conductivity.
[0165] The contact angle of the aerogel particles having a hydrophobic surface with water is usually 100 degrees or more, 110 degrees or more, 130 degrees or more, or 150 degrees or more.
[0166] Aerogel particles having a hydrophobic surface are preferably used as the thermally insulating inorganic particles in the present disclosure. Specifically, silica aerogel having a porous structure and a surface area of about 300 m according to BET is used. 2 / g~about 1000m 2 / g, preferably 500m 2 / g~about 1000m 2 / g,700m 2 / g~800m 2 / g, and the porosity is at least 80%, preferably 85% or more, and more preferably 90% or more.
[0167] The average particle size of the hydrophobic aerogel particles used as thermal insulation inorganic particles is usually 5 to 200 μm, preferably 5 to 150 μm, and more preferably 10 to 100 μm. The particle density is preferably 100 to 200 g / cm 3 .
[0168] By using the aerogel particles having the above-mentioned size, it is possible to improve the yield of the thermal insulation / flame retardant sheet produced by a papermaking process and provide a lightweight thermal insulation / flame retardant sheet having excellent thermal insulation properties.
[0169] In a certain manufacturing method, aggregates with a size of more than 200 μm to several millimeters may be produced. In this case, such aggregates are crushed to obtain aerogel particles with the above-mentioned size.
[0170] If individual aerogel particles in an inorganic powder have a hydrophobic surface and high surface tension, the particles will aggregate together in a papermaking suspension. As a result, the aerogel is difficult to uniformly mix with other ingredients in the slurry, such as inorganic fibers and thermoplastic resin fibers. In the present disclosure, this problem is solved by hydrophilizing the hydrophobic silica aerogel.
[0171] Methods for hydrophilizing the hydrophobic aerogel include: mixing the hydrophobic aerogel with an organic solvent or a surfactant to make the hydrophobic surface miscible with water; and coating the entire or partial surface of the hydrophobic aerogel particles with a hydrophilic polymer that does not penetrate the pores of the particles.
[0172] The organic solvent or surfactant used for hydrophilization is a solvent or surfactant that can exist at the interface between water and silica aerogel but does not affect the aggregation of silica aerogel particles. In addition, the solvent is miscible with the fiber in water.
[0173] Specific examples include polyol alkyl ether-based organic solvents having about 3 to 7 carbon atoms, such as ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, and diethylene glycol monomethyl ether.
[0174] In this regard, alkylene oxide-based surfactants such as polyoxyethylene, polyoxypropylene, and polyoxyethylene / polyoxypropylene condensates can enhance the hydrophilicity of aerogels, however, the hydrophilized aerogels tend to separate from the fiber-containing liquid phase with water as the solvent, which means that the aerogel particles may not be uniformly mixed with the fibers.
[0175] When the organic solvent or surfactant is included, its content in the aerogel slurry described below is preferably 10 wt% or less. If the content of the surfactant or organic solvent is too high, foaming may occur during the preparation of the papermaking slurry, especially during the mixing and stirring process.
[0176] Examples of hydrophilic polymers used for hydrophilization treatment include: polysaccharides, such as cellulose nanofibers, starch, amylose, cationized starch and carboxymethyl cellulose; and vinyl hydrophilic polymers, such as polyvinyl alcohol, polyvinyl acetate, ethylene-vinyl alcohol resin and polyacrylic acid. Among them, water-soluble polymers are preferred, and water-soluble polymers having multiple primary or secondary hydroxyl groups are more preferred. Further, for saponification products such as polyvinyl alcohol, from the viewpoint of water solubility, the saponification degree is preferably 77 to 99 mol%.
[0177] As polyvinyl alcohol, not only unmodified polyvinyl alcohol but also modified polyvinyl alcohol having multiple alcoholic hydroxyl groups in the side chain or having oxyalkylene groups, sulfonic acid groups, etc. in the side chain can be used, as long as the water solubility and hydrophilicity of the polyvinyl alcohol are not impaired by the modification.
[0178] These hydrophilic polymers are used in the form of aqueous solutions. These hydrophilic polymers act as thickeners, increasing the viscosity of the solution. The high viscosity aqueous solution can be stirred and shaken to evenly coat the aerogel particles, thereby producing aerogel particles with a hydrophilic surface.
[0179] Typical hydrophilic polymers have relatively long chains compared to the pore size of the aerogel and have multiple hydrophilic functional groups. Based on such a molecular structure, the hydrophilic polymer will wrap the aggregates of the aerogel particles, while the hydrophilic functional groups face the solvent as the dispersion medium. Therefore, the hydrophilized aerogel particles can have a temporary surface that is miscible with the medium containing the aerogel slurry. As a result, the aerogel particles in the form of aggregates can be dispersed in the solvent of the slurry.
[0180] A necessary and sufficient amount of hydrophilic polymer can be used to produce a temporary hydrophilic surface covering the hydrophobic aerogel particle aggregate. The usual amount of hydrophilic polymer used for this purpose is in the range of 1 / 2 to 1 / 100 in terms of the weight ratio of hydrophilic polymer to hydrophobic aerogel particles. The amount can be appropriately selected within the above range depending on the type of hydrophilic polymer and hydrophobic aerogel particles.
[0181] Among the above hydrophilization methods, the method using a water-soluble polymer is environmentally friendly, easy to operate and better for the manufacturing environment, and is therefore preferred. In this method, water can be used alone as a dispersion medium for the fiber-containing liquid and the papermaking suspension. This can simplify the wastewater treatment during the dehydration process.
[0182] The surfactants or hydrophilic polymers suitable for hydrophilizing the aerogel particles can also be used as organic binders or emulsifiers in the papermaking process. However, the above surfactants and hydrophilic polymers are handled differently when preparing the papermaking suspension. When used as a binder or emulsifier, the surfactant or hydrophilic polymer is usually added to the fiber-containing liquid, and then the aerogel is added simultaneously and gradually. The specific gravity of the aerogel and the aqueous phase (containing the surfactant or hydrophilic polymer) is very different, so the above treatment usually results in the separation of the aerogel and the aqueous phase.
[0183] When a water-soluble polymer is used as a hydrophilizing agent for aerogel, the problem associated with the difference in specific gravity does not occur. This is because the slurry containing aerogel and the hydrophilic polymer and the fiber-containing liquid are prepared separately and then mixed. In this case, the hydrophilic polymer can coat the aerogel particles and help the aerogel particles to disperse in the fiber-containing liquid, thereby obtaining a dispersion in which the aerogel particles are uniformly distributed throughout the fiber-containing liquid phase.
[0184] (5-2) Hydrophilic Silica Nanoparticles
[0185] The hydrophilic silica nanoparticles used in the present disclosure are generally wet-process silica or precipitated silica, which is synthesized in water using raw materials including mineral acids and sodium silicate synthesized from silica sand and soda ash. The hydrophilic silica nanoparticles aggregate and form amorphous agglomerates before mixing with the fiber-containing liquid. The agglomerates of the nanoparticles have a macroporous structure and can function as porous particles.
[0186] No special surface treatment is required to use hydrophilic silica nanoparticle clusters as thermally insulating inorganic particles.
[0187] For hydrophilic aerogel particles composed of silica nanoparticles, the silica nanoparticles have a hydrophilic surface and a primary average particle size of about 1 to 50 nm, particularly about 5 to 30 nm. The hydrophilic aerogel particles composed of silica nanoparticles are agglomerates (secondary particle clusters) with a particle size of about 100 nm to 100 μm. The nanoparticles in the agglomerates are not bound to each other, so the agglomerates can be broken into nanoparticles that are easily dispersed in water, and in the preparation process of papermaking suspensions, the nanoparticles are miscible with inorganic fibers such as silica inorganic fibers and glass fibers. Therefore, it is easy to obtain a suspension in which hydrophilic silica nanoparticles and inorganic fibers are entangled.
[0188] On the other hand, the silica nanoparticles in the agglomerates are not bound to each other, so the agglomerates can be broken into individual nanoparticles by a mixing operation such as stirring. If the nanoparticles or their agglomerates are not sufficiently entangled with the inorganic fibers, the binder and / or the fibrous mineral, some individual nanoparticles may flow out with water in the papermaking process because their size is reduced to a size smaller than the mesh size of the net used in the dewatering process. As a result, the yield in the papermaking process tends to decrease.
[0189] (5-3) Content of thermal insulation inorganic particles
[0190] Although insulating inorganic particles are not required, they are preferably included in the insulating / flame retardant sheet of the present disclosure. Under normal conditions where the atmospheric temperature rises to a maximum of 200°C, the hydrophilized silica aerogel particles can enhance the thermal insulation performance. If one of the multiple battery cells stacked in a battery pack or battery module overheats, the silica aerogel can slow down the transfer of heat energy to an adjacent battery cell or battery module. Further, the silica aerogel as a porous particle helps to make the insulating / flame retardant sheet lighter.
[0191] On the other hand, hydrophilized silica aerogel as an insulating inorganic particle can exert thermal insulation performance based on the low thermal conductivity of air pockets, however, at high temperatures (about 1000°C) where thermal runaway may occur, hydrophilized silica aerogel may not bring significant thermal insulation performance. Silica inorganic fibers and fiber minerals with heat resistance of more than 1000°C show flame retardancy and heat resistance at high temperatures. Therefore, in order to achieve thermal insulation and flame retardancy in a high temperature range covering both thermal runaway and conventional use, the content of the insulating inorganic particles is 0% by weight or more, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more and 45% by weight or less, 40% by weight or less. If the content exceeds more than half of the sheet material, papermaking becomes difficult, and the heat-insulating / flame-retardant sheet may not have sufficient heat resistance and flame retardancy at high temperatures under thermal runaway.
[0192] (6) Thermosetting resin precursor
[0193] The heat-insulating / flame-retardant sheet of the present invention may optionally contain a thermosetting resin precursor. The thermosetting resin precursor is a monomer or oligomer of a thermosetting resin such as a phenolic resin (e.g., a resol phenolic resin), a polyimide resin, a melamine resin, a diallyl phthalate resin, etc. The thermosetting resin precursor is in liquid or powder form.
[0194] Thermosetting resin precursors can be cured by heating or by a cross-linking reaction in the presence of a curing agent.
[0195] In the case of giving a desired shape to a heat insulating / flame retardant sheet or improving the strength of the sheet by laminating a thermosetting resin layer on the heat insulating / flame retardant sheet, it is preferred to add a thermosetting resin precursor to a papermaking suspension containing inorganic fibers (silica fibers, glass fibers), an organic binder and / or an inorganic binder and inorganic particles (fibrous minerals, heat insulating inorganic particles) to prepare the sheet. The resulting sheet containing the thermosetting resin precursor can be at least partially adhered to the laminated thermosetting resin layer by a crosslinking reaction between the sheet and the laminated thermosetting resin layer during the thermal curing process, thereby enhancing interlayer adhesion in the laminate.
[0196] The thermosetting resin precursor may be contained in an amount of less than 5 wt %, preferably 1 to 3 wt %, in terms of content. The greater the content, the greater the bonding strength to the thermosetting resin layer in the laminate, but since the sheet material mainly includes inorganic fibers, the flexibility of the resulting inorganic fiber-based thermal insulation / flame retardant sheet may not be ensured.
[0197] (7) Other fillers
[0198] In addition to the above-mentioned solid components, the papermaking suspension may also contain other solid fillers in an amount of less than 10% by weight, preferably less than 5% by weight, more preferably less than 3% by weight, relative to the total solid content.
[0199] Other fillers may include clay minerals (phyllosilicates) other than the above-mentioned fiber minerals. For example, hydrous ferrosilicate minerals such as mica, kaolinite, montmorillonite, sericite, illite, glauconite, chlorite, talc, or mixtures thereof may be included. Among them, montmorillonite, montmorillonite, bentonite, and mixtures thereof are preferably used.
[0200] Bentonite is a natural clay mineral, the main component of which is montmorillonite. Montmorillonite is a general term for a class of 2:1 type minerals, including montmorillonite, stevensite, hectorite, etc.
[0201] The crystal unit crystal of montmorillonite is a flat unit composed of tetrahedral sheets, octahedral sheets or tetrahedral sheets. Multiple such crystal units are stacked together to form a layered structure. Like sepiolite, montmorillonite is based on montmorillonite crystal units and enters the interfiber space of papermaking suspension. The montmorillonite crystal unit is a very thin lamellar crystal with a thickness of about 1nm and a width of 100 to 1000nm. After the suspension is dried, the solidified montmorillonite can exist in the interfiber space like a film, thereby acting as a binder for the fibers.
[0202] Montmorillonite has a high liquid limit and can absorb a relatively large amount of water. Montmorillonite has a swelling property that expands when water or an organic solvent enters the interlayer, and can absorb a large amount of water between the layers (for example, 10 times more water than kaolin). Further, montmorillonite is easily peptized in the presence of electrolytes. Therefore, by using it together with sepiolite, montmorillonite can show high film-forming properties and can form a film in the gaps between the fibers into which the inorganic particles enter.
[0203] The layered silicate used for papermaking suspension exists in a powder state, with an average particle size of 300 μm or less, preferably 200 μm or less, and more preferably a circle equivalent diameter of 10 to 100 μm. The layered silicate powder becomes viscous, sticky and plastic after mixing with water, and can spontaneously form a film. During the papermaking and drying process, the clay solidifies and solidifies, while inorganic particles such as inorganic adhesives and insulating inorganic particles are trapped in the inter-fiber space. The layered silicate (clay) can act as a binder for inorganic fibers and enhance the bonding force between inorganic fibers and inorganic particles, so that the inorganic fibers and inorganic particles can be stably maintained in the resulting paper.
[0204] Other examples of other solid fillers include neutralizers, lubricants, anti-caking agents, flow improvers, release agents, flame retardants, colorants, wetting agents, tackifiers, retention aids, paper strength enhancers, filters, pH adjusters, and the like.
[0205] (8) Dispersion medium
[0206] Any dispersion medium used for papermaking suspension can be used as long as it can uniformly dissolve or disperse the silica inorganic fibers, glass fibers, fibrous minerals, inorganic particles and organic fibers in the medium.
[0207] Examples of the dispersion medium include aromatic hydrocarbons such as toluene, ethers such as tetrahydrofuran, ketones such as methyl ethyl ketone, alcohols such as isopropyl alcohol, N-methyl-2-pyrrolidone (NMP), dimethylacetamide, dimethylformamide, dimethyl sulfoxide, water, and a mixture of one or more thereof.
[0208] In addition to water, an organic solvent may be mixed if necessary to improve particle dispersibility, but for reasons of environmental protection and simplified wastewater treatment, it is preferred to use only water. The content of the surfactant and the organic solvent is 0.1 wt % or less, preferably 0.01 wt % or less, and more preferably 0.001 wt % or less.
[0209] Even when aerogel particles hydrophilized by an organic solvent or a surfactant are used as the heat-insulating inorganic particles, the papermaking suspension can be maintained within the above range.
[0210] <Preparation of Papermaking Suspension>
[0211] The above-listed ingredients, i.e., silica inorganic fibers, glass fibers, fiber minerals and binders, as well as optional ingredients such as thermal insulation inorganic particles, thermosetting resins and other fillers, are added to a dispersion medium in required amounts and stirred to obtain a papermaking suspension. When preparing the papermaking suspension, water may be added for dilution, if necessary.
[0212] The solid content in the papermaking suspension can be selected to achieve uniform mixing of the components. Specifically, the solid content is 0.01 to 10% by weight, preferably 0.05 to 3% by weight.
[0213] The order of the ingredients in the mixing process is not particularly limited. The fibers and inorganic particles are preferably added to the dispersion medium while stirring the suspension.
[0214] When a hydrophobic material such as hydrophobic silica aerogel is used as the thermal insulating inorganic particles, it is preferred to prepare a slurry containing hydrophilized silica aerogel in advance, mix the aerogel slurry with a separately prepared fiber-containing liquid, and then add a binder to the mixed suspension.
[0215] Even if hydrophobic aerogel is used as the thermally insulating inorganic particles that may be separated from the aqueous phase containing fibers, the hydrophilized aerogel can be entangled with the fibers in the aqueous phase to obtain a sheet in which the hydrophobic aerogel is dispersed in the fibers.
[0216] <Wet papermaking>
[0217] Wet papermaking is a process for producing sheets or paper by using a paper machine to make paper from a suspension and removing the water by pressing and drying.
[0218] As the papermaking machine, a cylinder papermaking machine, a Fourdrinier papermaking machine, an inclined papermaking machine, an inclined short-wire machine, and a combination thereof can be used.
[0219] The dispersion medium is removed from the obtained wet-laid sheet by heating and drying. The drying temperature is a temperature at which the dispersion medium (water, and optionally an organic solvent) can be evaporated, and is preferably at least 80°C. The preferred upper limit of the drying temperature is lower than the temperature at which thermal curing is initiated in the case of a thermosetting resin precursor, and lower than the melting point in the case of a thermoplastic fiber. Therefore, depending on the type of thermoplastic resin fiber used and the presence or absence of a thermosetting resin precursor, the heating and drying process can be carried out at a temperature selected from the range of 60 to 200°C, preferably 80 to 150°C.
[0220] The heat insulating / flame retardant sheet can be formed into a desired shape after papermaking, before drying, during drying, or after drying. Drying can be performed by heating alone or by heating under pressure. Figure 3 When the separator sheet of the battery module shown in FIG. Figure 4 After the forming steps such as slitting shown, a pressing and drying step is performed.
[0221] The plastic wet-laid sheet can be formed into a slit sheet or a folded sheet before drying and then cured.
[0222] After drying, the formed sheet, like paper, can be subjected to further secondary processing such as cutting, punching and folding.
[0223] In addition to the above method, there is another method, which is called external addition method. In the external addition method, a liquid containing fibers, heat-insulating inorganic particles, fiber minerals and adhesives is applied to the sheet with a sprayer, a curtain coater, a dip coater, a rod coater, a roller, a scraper, etc. to impregnate them in the sheet. However, a certain amount of fiber minerals and inorganic particles tend to remain on the surface of the sheet and become powdery in the dry sheet, causing them to scatter. According to the present invention, the sheet is manufactured by a papermaking process, so the fiber minerals and heat-insulating inorganic particles can be retained in the resulting sheet by inorganic fibers as the main component. Inorganic particles and fiber minerals are entangled with fibers or fiber minerals. This can enhance their retention in the sheet and prevent the powdery particles generated after drying from scattering. In other words, the inorganic particles are stably retained in the sheet.
[0224] <Composition of thermal insulation / flame retardant sheet>
[0225] According to the present invention, the papermaking suspension having the above composition is made into a wet-laid sheet by a wet papermaking technique and then dried to remove the dispersion medium, thereby obtaining a heat-insulating / flame-retardant sheet.
[0226] In obtaining Figure 4 In the case of the sheet 9 having a plurality of slits shown, the wet-laid sheet is dried using a die having a convex portion for forming the slits. The heat-insulating / flame-retardant sheet of the present disclosure has the strength and flexibility required for the drying process through a die.
[0227] The thickness of the sheet is greater than 0.5 mm, 0.8 mm or more, 1 mm or more, 1.3 mm or more, 1.5 mm or more, and less than 3 mm, 2.5 mm or less, 2.0 mm or less, or 1.8 mm or less. If the sheet is too thin, its strength will be reduced. In addition, for a sheet that is too thin, the content of fibers and heat-insulating inorganic particles is reduced, and its heat-insulating performance may be unsatisfactory.
[0228] However, the fiber mineral can improve the strength of sheets with a thickness of less than 3 mm. Further, the thermoplastic resin fibers in the sheet can become plastic and soften when heated, thereby potentially improving the durability of the sheet during compression. Further, the heat-insulating inorganic particles can be held by the entangled fibers, so that the scattering of inorganic particle powder can be suppressed even during cutting or punching.
[0229] According to the present invention, the heat insulation / flame retardant sheet produced by papermaking technology can be used alone or in a laminate with a release paper. The release paper can be laminated to one side of the sheet by an adhesive. Figure 2 As shown, in the case of adhering the heat insulating / flame retardant sheet to the cover 12'a of the outer shell 12' of the battery module, an adhesive is applied to one side of the heat insulating / flame retardant sheet 10 to form an adhesive layer 10a, and then a release paper is laminated on the adhesive layer 10a. The release paper is peeled off from the heat insulating / flame retardant sheet 10, and then the sheet 10 is attached to the cover 12'a through the adhesive layer 10a. The work of applying the heat insulating / flame retardant sheet to the outer shell of the battery module can be simplified.
[0230] Compared with the sheet obtained by adding a binder to silica inorganic fibers in the papermaking process, the heat insulating / flame retardant sheet of the present disclosure having the above-mentioned constitution has excellent heat insulating properties in a high temperature range. Due to the presence of heat insulating inorganic particles, the heat insulating / flame retardant sheet can also exhibit excellent performance in conventional use (no thermal runaway occurs below 300°C).
[0231] Depending on the basis weight of the sheet, the bulk density of the thermal insulation / flame retardant sheet can be reduced to 400kg / m 3 Below, 300kg / m 3 Below, 250kg / m 3 Below and 100kg / m 3 Above or 150kg / m 3 Therefore, the bulk density is usually about 2000 kg / m 3 Compared with the mica sheet of the present invention, the heat insulation / flame retardant sheet of the present invention is significantly lighter. Because the heat insulation / flame retardant sheet is inserted between each battery cell in the battery pack and / or module, and a large number of battery cells are stacked on the battery pack and / or module, the heat insulation / flame retardant sheet of the present invention is significantly lighter. Figure 2 The light weight of the sheet is advantageous because the sheet is used in battery packs and modules as power sources for EV vehicles.
[0232] In the event that one of the battery cells experiences thermal runaway for some reason, the temperature of the battery cell will rise to a high temperature range where thermal insulation by aerogel may not be possible. Consuming the silica inorganic fibers through a dehydration condensation reaction can suppress the temperature rise in the early stages of thermal runaway, and because the thermal conductivity of the silica inorganic fibers is low, the temperature rise can be slowed down. This effect of the silica inorganic fibers can delay the spread of the thermal runaway event to adjacent battery cells, which is useful.
[0233] In addition, silica inorganic fibers can help maintain the shape of the sheet in the high temperature range of 600 to 800°C, while in this range, the strength of glass fibers decreases and it is difficult to maintain its fiber shape. This effect of silica inorganic fibers comes from its excellent heat resistance, which is higher than that of glass fibers. In addition, the fiber mineral can function as a flame retardant when exposed to flames.
[0234] Therefore, in the case of thermal runaway propagation (about 600-800°C) and under the condition of exposure to a flame close to 1000°C, the heat-insulating / flame-retardant sheet of the present disclosure can insulate in a wide temperature range from its conventional use to about 200°C, or even up to 1000°C, without changing its original sheet shape, for example, during a rapid temperature increase caused by thermal runaway of one battery cell. Therefore, the heat-insulating / flame-retardant sheet of the present disclosure can delay the heating of adjacent battery cells and the penetration of flames.
[0235] Furthermore, the thermal insulation / flame retardant sheet containing porous particles as thermal insulation inorganic particles has excellent durability against volume changes caused by volume fluctuations of lithium ion batteries. Even under normal conditions, lithium ion batteries undergo volume fluctuations such as expansion and contraction due to high or low temperatures. Figure 2 As shown, in a battery cell stacked battery pack, especially in a battery module where battery cells 11' are tightly stacked together in a housing 12', a heat insulating / flame retardant sheet containing porous particles as heat insulating inorganic particles can alleviate the volume fluctuation of battery cells.
[0236] <Purpose>
[0237] The heat-insulating / flame-retardant sheet of the present disclosure can be used for the following purposes. The heat-insulating / flame-retardant sheet is inserted between battery cells (such as Figure 1 When a battery consisting of a plurality of lithium-ion battery cells connected in series or in parallel is packaged in a battery housing with a certain space left outside the housing, a heat-insulating / flame-retardant sheet is placed between the battery and the cover of the housing to insulate the cover (as shown); Figure 2 As shown); thermal insulation / flame retardant sheet is used as Figure 3The partition walls or separator sheets of aligned cylindrical battery cells are shown.
[0238] If a battery cell or module experiences "thermal runaway", the electrolyte included in the battery will ignite, and in worse cases, the battery may explode or catch fire. Placing the thermal insulation / flame retardant sheet of the present disclosure between individual battery cells in a battery pack or battery module or in the space between a battery pack and a casing that wraps the battery pack can prevent the spread of thermal runaway. In other words, the thermal insulation / flame retardant sheet can prevent the thermal runaway event of a battery cell from spreading to adjacent battery cells and further to other batteries in the battery module.
[0239] Example
[0240] [Measurement and evaluation methods]
[0241] (1) Flame exposure test
[0242] like Figure 5 As shown, a sheet (150 mm × 150 mm) 15 to be evaluated is fixed on a steel plate 17 having an electrodeposited cationic coating, which is regarded as a battery cell box. It is fixed using an adhesive tape 16. The sheet 15 is heated by the flame of a horizontally fixed burner 14. The flame of the burner is positioned 5 mm from the surface of the sheet 15, and the temperature of the flame is adjusted to 1000°C. The temperature of the steel plate 17 (back temperature) is measured using a temperature sensor 13 placed on the back of the sheet. This surface is not directly exposed to the flame.
[0243] After heating with a burner for 10 minutes or 5 minutes, the state of the sheet, such as the presence or absence of cracks and the appearance of the sheet, was observed.
[0244] (2) Measuring thermal conductivity using heat flow technology
[0245] The three sheets prepared in the example (such as Figure 6 As shown in the figure, 31a, 31b and 31c) are sequentially placed and laminated on the heater 30. A thermocouple 32a is placed between the heater 30 and the bottom sheet 31a, another thermocouple 32b is positioned on the top of the sheet 31c, and a heat flow sensor 33 (K500B-20, manufactured by Kyoto Electronics Industry Co., Ltd.) is added to the thermocouple 32b. The temperature difference between the bottom surface of the bottom sheet 31a and the top surface of the top sheet 31c is measured by the thermocouples 32a and 32b, respectively, and the heat flow is measured by the heat flow sensor 33. The thermal conductivity (λ) is calculated based on these measurement results.
[0246] In the calculation of the thermal conductivity (λ), the sheet was heated at 200° C. for 6 hours using the heater 30 to uniformly heat the entire sheet, thereby measuring the temperature value of the sheet.
[0247] [Raw materials for thermal insulation / flame retardant sheets]
[0248] <Raw materials>
[0249] (1) Silica Inorganic Fiber
[0250] There are two cases with and without heat treatment as follows. BELCOTEX (registered trademark) 110 (composition: AlO 1.5 ·18[(SiO2) 0.6 (SiO 1.5 OH) 0.4 ]) of chopped fibers (fiber diameter 9 μm, fiber length 3 to 5 mm): one is the chopped fibers used after heat treatment at 300°C for 1 hour (sintered silica inorganic fibers), and the other is the chopped fibers used without heat treatment (unsintered silica inorganic fibers).
[0251] (2) Fiber Minerals
[0252] ·Meerschaum
[0253] Two types of sepiolite are used, alpha and beta.
[0254] The α-type sepiolite used was a powder having a bulk density of 0.13 to 0.15 g / ml, and 40% of the powder had a particle size of 150 μm or less.
[0255] The β-sepiolite used was a powder having a bulk density of 0.20 to 0.27 g / ml, and 80% of the powder had a particle size of 45 μm or less.
[0256] Potassium titanate
[0257] Tismo produced by Otsuka Chemical Co., Ltd. was used. Tismo is potassium titanate (whisker) having a fiber diameter of 0.3 to 0.6 μm and a fiber length of 10 to 20 μm.
[0258] (3) Glass fiber
[0259] Glass fibers (E glass) having a diameter of 5 to 9 μm and a length of 3 to 9 mm were used.
[0260] (4) Organic binder
[0261] ·Pulp fiber (fiber diameter 20-30 μm)
[0262] Polyester fiber (fiber diameter 5-10 μm, fiber length 3-9 mm)
[0263] Polyvinyl alcohol fiber (fiber diameter 5-12 μm, fiber length 3-6 mm)
[0264] Acrylic latex
[0265] (5) Inorganic adhesives
[0266] Aluminum sulfate
[0267] Colloidal Silica
[0268] SNOWTEX 30 (registered trademark) was used. SNOWTEX 30 is a colloidal solution with a specific surface area of 130 to 280 m 2 The silica nanoparticles (amorphous) of 1.4477 g / g are distributed in the form of individual particles with an average primary particle size of 10 to 20 nm.
[0269] (6) Insulating inorganic particles
[0270] The following two types of heat-insulating inorganic particles were used.
[0271] (6-1) Hydrophobic Aerogel
[0272] Amorphous silica produced by the sol-gel method has a surface contact angle of 120 to 150 degrees and a surface area of 700 to 800 m 2 / g, porosity is 120~150kg / m 3 , a hydrophobic aerogel having an average pore size of 20 nm, a particle size of 30 to 120 μm, and a DBP oil absorption of 540 to 650 g / 100 g. The hydrophobic aerogel is subjected to the following hydrophilization treatment I, II, or III. Each hydrophilized aerogel is used as the thermal insulating inorganic particle I, II, or III.
[0273] ·Insulating inorganic particles I
[0274] 20 g of the hydrophobic aerogel and 20 g of an organic solvent (ethylene glycol monobutyl ether) were added to 200 g of water, mixed and shaken to obtain an aerogel slurry. In the hydrophilization treatment, the organic solvent was used at a ratio of aerogel: organic solvent = 1: 1. The aerogel solid content in the obtained hydrophilized aerogel slurry was 8.3%.
[0275] ·Insulating inorganic particles II
[0276] 20 g of the above hydrophobic aerogel, 20 g of an aqueous solution of cellulose nanofibers having a concentration of 2.3%, and 20 g of an organic solvent (ethylene glycol monobutyl ether) were added to 200 g of water, mixed and shaken to obtain an aerogel slurry. In the hydrophilization treatment, the above cellulose nanofibers were used at a ratio of aerogel: cellulose nanofibers = 43:1. The aerogel solid content in the obtained hydrophilized aerogel slurry was 8.6%.
[0277] ·Insulating inorganic particles III
[0278] 30 g of the hydrophobic aerogel and 5 g of polyvinyl alcohol were added to 300 g of water to obtain an aerogel slurry. In the hydrophilization treatment, the polyvinyl alcohol was used at a ratio of aerogel: polyvinyl alcohol = 6: 1. The aerogel solid content in the obtained slurry was 8.9%.
[0279] (6-2) Hydrophilic silica particles (wet process silica)
[0280] As the heat-insulating inorganic particles IV, amorphous precipitated silica composed of hydrophilic silica nanoparticles and having a large number of silanol groups on the surface is used. The hydrophilic silica nanoparticles having an average primary particle size of several nanometers form amorphous aggregates as secondary particles with a diameter of 1 to 10 μm. The specific surface area of the aggregates is 200 to 250 m 2 / g, DOA oil absorption is 230~280ml / 100g.
[0281] (7) Others
[0282] ·Mica (Yamaguchi Mica AB-25S)
[0283] Wet grinding products
[0284] The average particle size is 24μm and the bulk density is 0.17g / ml
[0285] Kaolinite (research and experimental grade kaolin provided by Hayashi Pure Chemicals Co., Ltd.)
[0286] <Preparation of papermaking suspension and production of sheets No. 1 to 7 by papermaking technology, each sheet not containing insulating inorganic particles>
[0287] In a container filled with 2000 cc of water, the above raw material components were mixed in the proportions (weight % of solid content) shown in Table 1, and further, 2 cc of polyacrylamide was added as a flocculant, followed by stirring with a stirrer and forming a sheet by hand.
[0288] The wet-laid sheet thus obtained was placed in an oven and dried for 10 minutes at 100° C. The resulting square sheet having a length of 150 mm and a thickness of 1.5 mm was measured.
[0289] The sheet was subjected to a flame exposure test (exposure time: 10 minutes). One side was exposed to the flame, and the temperature of the back side not directly exposed to the flame was measured. The measured value was mathematically converted to a value for a sheet with a thickness of 1.6 mm, and the converted value was applied as the thermal insulation of the sheet. In addition, the appearance of the sheet after the test was visually observed. These results are shown in Table 1.
[0290] A mica sheet (commercially available product) as Reference Example R1 was evaluated in the same manner. The results are shown in Table 1.
[0291] Table 1
[0292]
[0293] Regarding Sheets No. 3, 4, and 7, the unsintered silica inorganic fibers contained therein undergo a dehydration condensation reaction, and therefore consume heat energy at high temperatures. The temperature of the back side of the sheet heated indirectly with a flame was relatively low, indicating a heat insulating effect. However, Sheet No. 3, which does not contain glass fibers or fiber minerals, was unable to shrink at high temperatures, and as a result, cracks were observed on the sheet after the test.
[0294] Sheet No. 5 is mainly composed of fibrous minerals and does not contain silica inorganic fibers. After the flame exposure test, no significant shrinkage or cracks were observed in the sheet. Regarding bulk density, although sheet No. 5 is lighter than mica sheets, it is relatively heavy compared to sheets mainly composed of silica inorganic fibers (such as No. 4). In addition, the thermal insulation of No. 5 is also inferior to that of sheets mainly composed of silica inorganic fibers.
[0295] No. 6 is a sheet material with glass fiber as the main component. Since glass fiber melts at 1000°C, for example, when exposed to flame, No. 6 cannot obtain satisfactory thermal insulation. After the flame exposure test, the original fiber shape of the glass fiber was no longer observed in the area directly exposed to the flame or around it, which confirmed that the glass fiber melted due to exposure to the flame.
[0296] On the other hand, sheets No. 1 and 2 using sintered silica inorganic fibers as the silica inorganic fibers did not shrink due to the flame exposure test. This indicates that shrinkage of the silica inorganic fibers can be avoided by performing heat treatment in advance. No cracks were observed in sheet No. 1, while cracks were observed in sheet No. 2. These observations indicate that, since sepiolite has a fibrous morphology, it is able to entangle with other fibers and can accommodate the volume expansion of the steel plate heated by the flame. In contrast, mica, which has a flat shape, cannot be entangled with other fibers.
[0297] The heat insulation effect of sheets No. 1 and 2 using sintered silica inorganic fibers is not as good as that of sheets No. 3 and 4. This result indicates that the sintered silica inorganic fibers may not undergo dehydration condensation and fail to consume heat energy.
[0298] <Preparation of papermaking suspension, production and evaluation of sheets No. 21 to 27 containing heat-insulating inorganic particles>
[0299] In a container filled with 2000 cc of water, the above raw material components were mixed to prepare a papermaking suspension having the composition (weight % of solid content) shown in Table 2.
[0300] The order of adding or mixing the components is unsintered silica inorganic fiber, glass fiber, fiber mineral, organic fiber (PET fiber), thermal insulation inorganic particles, inorganic binder, and flocculant (polyacrylamide). The flocculent state of the papermaking suspension is confirmed while adding polyacrylamide in a range of 3cc to 18cc.
[0301] When hydrophobic heat-insulating inorganic particles I, II or III are used, a separately prepared slurry containing the hydrophilized heat-insulating inorganic particles is used. The amounts (weight %) shown in Table 2 are the solid contents in the papermaking suspension.
[0302] When hydrophilic silica particles are used as the heat-insulating inorganic particles, the silica particles in powder form are added to the fiber-containing liquid.
[0303] The papermaking suspension prepared above was poured into a wet forming machine (filter screen #80 (opening 180 to 200 μm)) and dehydrated by suction.
[0304] The dewatering net was heated and pressurized for 10 minutes using a hot press (100°C). In this way, a square sheet with a length of 150 mm on each side and a thickness of about 1.2 to 2.1 mm was obtained. Three sample sheets were produced using each papermaking suspension. The average yield calculated based on the solid content of the papermaking suspension was 80% to 90%.
[0305] The produced sheets were subjected to a flame exposure test, and after the flame exposure test (exposure time: 5 minutes), the thermal conductivity (heat flow method) was measured. The back surface temperature was mathematically converted to reflect the sheet thickness of 1.6 mm, and the converted value was used. The average value was calculated from the converted values of three sheets and is shown in Table 2. In addition, the appearance of the sheet after the flame exposure test was visually observed, such as the presence or absence of cracks. The results are shown in Table 2.
[0306] Table 2 also shows the thermal conductivity of the sheet when the heat source is 200°C.
[0307] Reference Example R2:
[0308] The hydrophobic aerogel particles (powder) without hydrophilization treatment are directly added to the fiber-containing liquid. Even if shaken and stirred, the powder of the hydrophobic aerogel particles floats on the water surface, in other words, the powder phase composed of the hydrophobic aerogel particles is separated from the water phase. As a result, it is impossible to obtain a papermaking suspension in which the fibers and the aerogel particles are in a uniformly mixed state.
[0309] Reference Example R3:
[0310] As a hydrophilizing agent, a polyoxyethylene / polyoxypropylene condensate as a nonionic surfactant was used. 10 g of the hydrophilizing agent was added to 100 g of water, and then 10 g of hydrophobic aerogel particles (powder) were added, followed by vigorous shaking to obtain a slurry containing thermally insulating inorganic particles. The aerogel-containing slurry thus prepared was added to a fiber-containing liquid prepared separately, however, the aerogel-containing slurry was separated from the fiber-containing liquid regardless of stirring, and as a result, a uniformly mixed liquid (papermaking suspension) could not be obtained.
[0311] Table 2
[0312]
[0313] With regard to thermal conductivity at a heat source of 200°C, sheets No. 21 to 24, 26 and 27 containing hydrophilized aerogel particles as thermal insulating inorganic particles are superior to sheet No. 25 containing hydrophilized nanoparticles as thermal insulating inorganic particles. This superiority may be due to the presence of hydrophilized aerogel particles throughout the sheet, and since air pockets have significantly lower thermal conductivity, the highly porosity hydrophobic aerogel particles contained in the sheet can exhibit excellent thermal insulation.
[0314] Further, from the comparison between No. 27 and No. 23, the thermal conductivity of the sheet mainly composed of silica inorganic fibers is lower than that of the sheet mainly composed of glass fibers. This result may be due to the lower thermal conductivity of silica inorganic fibers.
[0315] Regarding the back surface temperature of the sheet after the flame exposure test, the temperatures of sheets No. 21, 22, 23, 24, 26, and 27 each containing hydrophilized aerogel particles as the heat-insulating inorganic particles were lower than that of sheet No. 25.
[0316] This thermal insulation effect may come from the hydroxyl-containing silica fibers in addition to the hydrophilized aerogel particles. The hydrophilized aerogel particles can exhibit thermal insulation properties under normal conditions where the ambient temperature is below 200°C. In the event of a temperature surge caused by thermal runaway, the silica fibers can delay the rapid temperature rise, and the aerogel particles can exhibit thermal insulation properties. Therefore, the temperature surge of the entire sheet can be slowed down.
[0317] After the flame exposure test, no cracks were observed in the sheets Nos. 21 to 27. This result may be due to the fact that the sheets contained unsintered silica fibers and glass fibers at a glass fiber / silica fiber ratio of 1 / 10 or more.
[0318] In the case where the content of glass fiber is too high relative to the content of silica fiber, the glass fiber will melt under flame exposure. As can be seen from sheet No. 27, its glass fiber / silica fiber content ratio is not less than 8 / 1.
[0319] However, sheet No. 23 lacking clay minerals and having a content ratio of glass fiber to silica fiber (glass fiber / silica fiber) greater than 1 / 7 lost its sheet shape when exposed to flame and decomposed into soft, fluffy masses.
[0320] From the comparison between No.22 and No.26, it is considered that the use of fibrous mineral as the clay mineral can impart higher thermal insulation. The superiority of the fibrous mineral in the thermal insulation effect can be recognized not only in conventional use, but also in the case of exposure to flames. In conventional use, heat energy can be consumed by dehydration of water absorbed in the sepiolite. Because the fibrous mineral can increase the open pores of the resulting sheet compared to planar minerals, the porosity of the entire sheet of sheet No.22 using fibrous minerals may be higher than that of sheet No.26. In the medium and high temperature range exposed to flames, there are many open pores in the sheet, so more heat energy can be released. Note that sheet No.26 has low hardness and relatively low strength compared to other sheets, so the handling performance is poor.
[0321] Figure 7 and Figure 8 The cross-sections of sheets No. 21 and No. 23 in the thickness direction, taken with an electron microscope (magnification 1000 times), are shown respectively.
[0322] As can be seen in these micrographs, the insulating inorganic particles are present throughout the sheet, interwoven with the fibers or embedded in the spaces between the fibers.
[0323] Fig. 9 and Fig.10 The photographs of the heated surfaces of Sheets No. 21 and No. 23 in the flame exposure test taken with an electron microscope (magnification 1000 times) are respectively shown.
[0324] It can be confirmed from these micrographs that the silica inorganic fibers, the heat insulating inorganic particles and the fibrous clay minerals (in the case of No. 21) are still able to remain.
[0325] <Comparison of Thermal Insulation Performance between Silica Inorganic Fiber and Glass Fiber>
[0326] The heat insulation test of the heat insulation / flame retardant sheets No. 23 and No. 27 produced above was carried out by heating to 700°C in the following manner.
[0327] (1) Thermal insulation test I
[0328] like Fig.11 As shown in FIG. 1 , a ceramic heat insulating plate 23 (300 mm square and 15 mm thick) having a circular opening 23a with a diameter of 40 mm was placed on a hot plate 22 (100 mm square) at a temperature of 700° C. Then, a sheet 21 (150 mm square) was placed on top of the plate 23 and positioned in such a way that the center of the sheet 21 was aligned with the center of the circular opening 23a of the plate 23. After holding for 6 minutes, the sheet was evaluated.
[0329] Fig.12 , Fig.13 Photographs of the heated portions of sheets No. 23 and 27 after the test are respectively shown.
[0330] Comparing the two, sheet No. 23 maintained its state after papermaking, while the glass fibers in sheet No. 27 lifted from the sheet plane due to reduced elasticity, indicating that the shape of the sheet in the heated portion could not be maintained.
[0331] The heated surfaces of sheets No. 23 and 27 were photographed using a microscope (magnification 100 times) and Fig.14 and 15 The other side (referred to as the back side) of sheet No. 23 and 27 was photographed using a microscope (magnification 100 times) and the Fig.16 and 17 Shown in.
[0332] Regarding sheet No.27, Fig.15 (heating surface) and Fig.17 (Back) By comparison, it can be seen that the heated surface has more melted and fused parts, and the melted and fused parts have a larger area. Regarding sheet No. 23, most of the fibers still maintain their fiber shape even on the heated surface ( Fig.14 and 16 ). Sheet No. 27 is mainly composed of glass fibers. Some of the glass fibers in Sheet No. 27 begin to melt at 700°C, and the elasticity and strength decrease. Therefore, the interweaving between the fibers that remain in the fiber state decreases, and as a result, the remaining fibers may be lifted from the plane of the sheet.
[0333] (2) Thermal insulation test II
[0334] like Fig.18 As shown, the heat insulating / flame retardant sheet 21' (150 mm x 150 mm) to be evaluated is placed on a SUS plate 22' (100 mm x 100 mm) equipped with a heater, and a thermocouple 24' is placed on the sheet positioned at the corresponding position of the heater. Then, the temperature of the plate and the temperature of the sheet are measured.
[0335] The thermal insulation properties were measured in the range of 200° C. to 500° C. by increasing the temperature of the heater by 100° C. At each temperature, the sheet was heated for 10 minutes. Fig.19 The results of the sheet temperature during the process of increasing the heater temperature are shown: the dashed line indicates the temperature of the heater, the solid line indicates the temperature of sheet No. 23, and the dotted line indicates the temperature of sheet No. 27.
[0336] During the heating process in the range of 300° C. to 500° C., the temperature of sheet No. 23 was always about 3 to 6° C. lower than that of sheet No. 27. This indicates that the dehydration condensation of the silica inorganic fibers can delay the temperature rise.
[0337] <Appendix>
[0338] The present invention also includes various modified embodiments that can be conceived by those skilled in the art based on the above preferred embodiments and examples. The present invention includes the following embodiments.
[0339] 1. A heat-insulating / flame-retardant sheet having a thickness of 3 mm or less, comprising:
[0340] 25 to 70% by weight of silica inorganic fibers having hydroxyl groups;
[0341] 2 to 25% by weight of glass fiber;
[0342] 5 to 40% by weight of fibrous minerals; and
[0343] 3 to 20% by weight of a binder.
[0344] 2. A heat-insulating / flame-retardant sheet having a thickness of 3 mm or less, comprising:
[0345] 25 to 70% by weight of silica inorganic fibers having hydroxyl groups;
[0346] 2 to 25% by weight of glass fiber;
[0347] 5 to 40% by weight of fibrous minerals;
[0348] 3 to 20% by weight of a binder; and
[0349] Greater than 0 to 45% by weight of thermally insulating inorganic particles,
[0350] The heat-insulating inorganic particles include hydrophilized aerogel particles, which are obtained by treating the surface of hydrophobic aerogel particles having a porosity of 80% or more and an average particle size of 5 to 200 μm with a hydrophilizing agent.
[0351] 3. The heat-insulating / flame-retardant sheet according to embodiment 1 or 2, wherein a weight content ratio of the inorganic silica fibers to the glass fibers (inorganic silica fibers / glass fibers) is 30 / 1 to 1.5 / 1.
[0352] 4. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 3, wherein the thickness of the thermal insulation / flame retardant sheet is greater than 0.5 mm.
[0353] 5. The heat-insulating / flame-retardant sheet according to any one of embodiments 2 to 4, wherein the contact angle between the hydrophobic aerogel particles of the hydrophobic aerogel and water is 100° or more.
[0354] 6. The thermal insulation / flame retardant sheet according to embodiment 5, wherein the hydrophilized aerogel particles are obtained by contacting the surfaces of the hydrophobic aerogel particles with an organic solvent, a surfactant, or a hydrophilic polymer.
[0355] 7. The heat-insulating / flame-retardant sheet according to embodiment 6, wherein the hydrophilized aerogel particles are obtained by coating at least a portion of the surface of hydrophobic silica aerogel particles having a porosity of 90% or more and an average particle size of 5 to 200 μm with a hydrophilic polymer.
[0356] 8. The heat-insulating / flame-retardant sheet according to any one of embodiments 5 to 7, wherein the surface area of the hydrophobic aerogel particles is 300 to 1000 m 2 / g.
[0357] 9. The heat-insulating / flame-retardant sheet according to any one of embodiments 5 to 8, wherein the particle density of the hydrophobic aerogel particles is 100 to 200 g / cm 3 .
[0358] 10. The thermal insulation / flame retardant sheet according to any one of embodiments 5 to 9, wherein the hydrophilic polymer is a polymer having a plurality of hydroxyl groups.
[0359] 11. The thermal insulation / flame retardant sheet according to embodiment 10, wherein the hydrophilic polymer is a water-soluble polymer.
[0360] 12. The heat-insulating / flame-retardant sheet according to embodiment 10 or 11, wherein the amount of the hydrophilic polymer in the hydrophilized aerogel particles relative to the amount of the hydrophobic aerogel particles is 1 / 2 to 1 / 100 in terms of a weight ratio of hydrophilic polymer / hydrophobic aerogel particles.
[0361] 13. The thermal insulation / flame retardant sheet according to any one of embodiments 2 to 12, wherein the thermal insulation inorganic particles further comprise nanoparticles having a hydrophilic surface and an average primary particle size of 1 nm to 50 nm.
[0362] 14. The heat-insulating / flame-retardant sheet according to any one of embodiments 1 to 13, wherein the fibrous mineral is at least one selected from the group consisting of sepiolite, palygorskite, potassium titanate whiskers, and wollastonite.
[0363] 15. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 13, wherein the fibrous mineral is potassium titanate whisker or wollastonite.
[0364] 16. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 13, wherein the fibrous mineral is a layered silicate mineral.
[0365] 17. The heat-insulating / flame-retardant sheet according to embodiment 16, wherein the silicate mineral is α-type sepiolite or β-type sepiolite.
[0366] 18. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 17, wherein the binder comprises thermoplastic resin fibers.
[0367] 19. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 18, wherein the binder comprises an organic flocculant.
[0368] 20. The thermal insulation / flame retardant sheet according to any one of embodiments 1 to 19, wherein the binder comprises an inorganic binder.
[0369] 21. The thermal insulation / flame retardant sheet according to embodiment 20, wherein the inorganic binder comprises colloidal silica.
[0370] 22. The thermal insulation / flame retardant sheet according to embodiment 20 or 21, wherein the inorganic binder comprises an inorganic metal salt.
[0371] 23. The heat-insulating / flame-retardant sheet according to any one of embodiments 1 to 22, wherein the bulk density is 100 to 400 kg / m 3 .
[0372] 24. A method for producing a heat-insulating / flame-retardant sheet, comprising the following steps:
[0373] A hydrophilized aerogel slurry is prepared by dispersing silica aerogel particles having a hydrophobic surface, a porosity of 80% or more and an average particle size of 5 to 200 μm in an aqueous solution containing a hydrophilizing agent;
[0374] Adding and mixing the hydrophilized aerogel slurry into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder to prepare a suspension containing 25 to 70 weight percent of silica inorganic fibers, 2 to 25 weight percent of glass fibers, 5 to 40 weight percent of fiber minerals, 3 to 20 weight percent of a binder, and more than 0 to 45 weight percent of the hydrophilized aerogel; and
[0375] The suspension is used to carry out a papermaking process to obtain a sheet having a thickness of less than 3 mm.
[0376] 25. A method for producing a heat-insulating / flame-retardant sheet according to any one of embodiments 2 to 23, comprising the following steps:
[0377] A hydrophilized aerogel slurry is prepared by dispersing silica aerogel particles having a hydrophobic surface, a porosity of more than 80% and an average particle size of 5 to 200 μm in an aqueous solution of a water-soluble polymer;
[0378] adding and mixing the hydrophilized aerogel slurry into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder containing thermoplastic resin fibers; and
[0379] The obtained liquid mixture is used to carry out a papermaking process, followed by heating and pressurization to obtain a sheet having a thickness of less than 3 mm.
[0380] 26. The method for producing a thermal insulation / flame retardant sheet according to embodiment 24 or 25, further comprising the step of adding an inorganic binder and / or an organic flocculant to the obtained suspension or liquid mixture.
[0381] 27. The method for producing a heat-insulating / flame-retardant sheet according to any one of embodiments 24 to 26, wherein the content of the surfactant in the hydrophilized aerogel slurry is 10 wt % or less.
[0382] 28. The method for producing a heat-insulating / flame-retardant sheet according to any one of embodiments 24 to 27, wherein the hydrophilized aerogel slurry contains an organic solvent in an amount of 10 wt % or less.
[0383] 29. The method for producing a heat-insulating / flame-retardant sheet according to any one of embodiments 1 to 28, wherein the dispersion medium of the aqueous dispersion is water.
[0384] 30. A battery pack or a battery module, comprising: a plurality of battery cells connected in series or in parallel and accommodated in a housing; and the sheet according to any one of embodiments 1 to 23 interposed between the battery cells.
[0385] 31. A battery pack or battery module, comprising: a plurality of battery cells connected in series or in parallel and housed in a housing; and a sheet according to any one of embodiments 1 to 23, wherein the sheet is adhered to an inner wall of the housing in contact with the battery cells.
[0386] Industrial Applicability
[0387] The heat-insulating / flame-retardant sheet of the present invention is a thin and light sheet like paper, which can be inserted between battery cells of a battery pack including a plurality of lithium-ion battery cells, and in particular, between battery cells of a battery module that wraps the battery pack, the battery pack including a plurality of battery cells stacked in a housing. In normal use, the sheet isolates the heat energy of a battery cell with an increased temperature from adjacent battery cells. Furthermore, when a thermal runaway event occurs in a battery cell, the sheet inserted between the battery cells can prevent the thermal runaway from spreading to other battery cells in the battery module.
[0388] Description of Reference Numerals
[0389] 9.10 Heat insulation / flame retardant sheet
[0390] 8, 11, 11' battery cells
[0391] 12 Shell.
Claims
1. A heat-insulating / flame-retardant sheet having a thickness of less than 3 mm, comprising: 25 to 70% by weight of silica inorganic fibers having hydroxyl groups; 2 to 25% by weight of glass fiber; 5 to 40% by weight of fibrous minerals; 3 to 20% by weight of a binder; and 0 to 45% by weight of thermal insulation inorganic particles, in, The heat-insulating inorganic particles include hydrophilized aerogel particles obtained by treating hydrophobic aerogel particles having a porosity of 80% or more and an average particle size of 5 to 200 μm with a hydrophilizing agent.
2. The heat-insulating / flame-retardant sheet according to claim 1, wherein: The weight content ratio of the inorganic silica fiber to the glass fiber, that is, the inorganic silica fiber / glass fiber is 30 / 1 to 1.5 / 1.
3. The heat-insulating / flame-retardant sheet according to claim 1 or 2, wherein: The hydrophilized aerogel particles are obtained by contacting the surfaces of the hydrophobic aerogel particles with an organic solvent, a surfactant or a hydrophilic polymer.
4. The heat-insulating / flame-retardant sheet according to claim 3, wherein: The hydrophilized aerogel particles include hydrophobic aerogel particles whose surfaces are coated with a hydrophilic polymer.
5. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 4, wherein: The weight ratio of the hydrophilic polymer to the hydrophobic aerogel particles in the hydrophilized aerogel particles is 1 / 2 to 1 / 100 (hydrophilic polymer / hydrophobic aerogel particles).
6. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 5, wherein: The fiber mineral is at least one selected from the group consisting of sepiolite, palygorskite, potassium titanate whisker and wollastonite.
7. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 6, wherein: The binder includes thermoplastic resin fibers.
8. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 7, wherein: The binder includes an organic flocculant.
9. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 8, wherein: The binder includes an inorganic binder.
10. The heat-insulating / flame-retardant sheet according to claim 9, wherein: The inorganic binder includes colloidal silica and / or an inorganic metal salt.
11. The heat-insulating / flame-retardant sheet according to any one of claims 1 to 10, having a bulk density of 100 to 400 kg / m 3 .
12. A method for producing a heat-insulating / flame-retardant sheet, comprising the following steps: A hydrophilized aerogel slurry is prepared by dispersing silica aerogel particles having a hydrophobic surface, a porosity of 80% or more and an average particle size of 5 to 200 μm in an aqueous solution containing a hydrophilizing agent; Adding and mixing the hydrophilized aerogel slurry into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder to prepare a suspension containing 25 to 70 weight percent of silica inorganic fibers, 2 to 25 weight percent of glass fibers, 5 to 40 weight percent of fiber minerals, 3 to 20 weight percent of a binder, and more than 0 to 45 weight percent of the hydrophilized aerogel; as well as The suspension is used to carry out a papermaking process to obtain a sheet having a thickness of less than 3 mm.
13. A method for producing a heat-insulating / flame-retardant sheet, the heat-insulating / flame-retardant sheet being the sheet according to any one of claims 1 to 11 and comprising the heat-insulating inorganic particles, the method for producing the heat-insulating / flame-retardant sheet comprising the following steps: A hydrophilized aerogel slurry is prepared by dispersing silica aerogel particles having a hydrophobic surface, a porosity of more than 80% and an average particle size of 5 to 200 μm in an aqueous solution of a water-soluble polymer; adding and mixing the hydrophilized aerogel slurry into an aqueous dispersion containing silica inorganic fibers having hydroxyl groups, glass fibers, fiber minerals, and a binder containing thermoplastic resin fibers; as well as The obtained liquid mixture is used to carry out a papermaking process, followed by heating and pressurization to obtain a sheet having a thickness of less than 3 mm.
14. The method for producing a heat-insulating / flame-retardant sheet according to claim 12 or 13, wherein: The hydrophilized aerogel slurry contains a surfactant in an amount of 10 wt % or less.
15. The method for producing a heat-insulating / flame-retardant sheet according to claim 12 or 13, wherein: The hydrophilized aerogel slurry contains an organic solvent in an amount of 10 wt % or less.
16. A battery pack or battery module, comprising: Multiple battery cells connected in series or in parallel; A shell encapsulating the battery cell; and a sheet according to any one of claims 1 to 11 placed between the battery cells.
17. A battery pack or battery module, comprising: Multiple battery cells connected in series or in parallel; A shell encapsulating the battery cell; and a sheet according to any one of claims 1 to 11 adhered between the inner surface of the outer case and the battery cell.
Citation Information
Patent Citations
Heat insulating material and method of manufacturing heat insulating material
JP2015163815A
Heat insulation material and manufacturing method of heat insulation material
JP2020200901A
Heat insulation sheet for battery pack and battery pack
JP2021034278A
Flame-resistant materials for electric vehicle batteries
JP2021531631A
Heat transfer suppression sheet and battery pack
JP6997263B1